2010
DOI: 10.1186/1477-7517-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Better retention of Malaysian opiate dependents treated with high dose methadone in methadone maintenance therapy

Abstract: BackgroundMethadone is a synthetic opiate mu receptor agonist that is widely used to substitute for illicit opiates in the management of opiate dependence. It helps prevent opiate users from injecting and sharing needles which are vehicles for the spread of HIV and other blood borne viruses. This study has the objective of determining the utility of daily methadone dose to predict retention rates and re-injecting behaviour among opiate dependents.MethodsSubjects comprised opiate dependent individuals who met s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The adoption of 6-month intervals to measure LFU was in accordance with the standard definition of LFU in HIV cohorts recommended by Chi et al 20 Nearly half of those lost to follow-up were lost during the first 6 months of the follow-up period in our study, a fact reported across many studies. [7][8][9][10][11]16 Retention improved progressively after the first 6 months; this was due to timely intervention by programme managers. The interim findings of the study were used to raise awareness about the problem of LFU, and to sensitise and motivate the MMT staff to perform better and train them in 'soft' skills, including better communication with participants and proactive follow-up (by telephone or home visits) of participants who missed doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of 6-month intervals to measure LFU was in accordance with the standard definition of LFU in HIV cohorts recommended by Chi et al 20 Nearly half of those lost to follow-up were lost during the first 6 months of the follow-up period in our study, a fact reported across many studies. [7][8][9][10][11]16 Retention improved progressively after the first 6 months; this was due to timely intervention by programme managers. The interim findings of the study were used to raise awareness about the problem of LFU, and to sensitise and motivate the MMT staff to perform better and train them in 'soft' skills, including better communication with participants and proactive follow-up (by telephone or home visits) of participants who missed doses.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Several studies on MMT retention and its associated factors from China and other countries have limitations related to short follow-up period, small sample size, limited representativeness and the retrospective nature of the study designs. [7][8][9][10][11] Information on HIV seroconversion rates among participants on MMT is scarce. The present study was conducted in a large cohort of HIV-negative persons enrolled into the MMT programme and followed for 2 and a half years across 13 clinics in Yunnan.…”
mentioning
confidence: 99%
“…The required dose for retention on treatment is 40 mg/day. Nevertheless, and in line with the above-mentioned studies, Mohamad recommended that a dose of 80 mg was the most likely to lead to successful treatment [13].…”
Section: Institutional Factorsmentioning
confidence: 94%
“…The patients were dichotomized into those receiving methadone more than 80 mg or less than 80 mg. The 80 mg cut-off was chosen since this is the consensus for high dose and low dose methadone grouping as proposed by previous studies 15 - 17 and our predetermined cut-off using Receiver Operating Curve (ROC) analysis 18 . All ECGs were performed 24 hours after last methadone dose with subjects remained supine for 5 minutes prior to ECG recording.…”
Section: Methodsmentioning
confidence: 99%